2018
DOI: 10.1021/acsnano.8b05151
|View full text |Cite
|
Sign up to set email alerts
|

Super-resolution Imaging of Proton Sponge-Triggered Rupture of Endosomes and Cytosolic Release of Small Interfering RNA

Abstract: The intracellular delivery of nucleic acids and proteins remains a key challenge in the development of biologic therapeutics. In gene therapy, the inefficient delivery of small interfering RNA (siRNA) to the cytosol by lipoplexes or polyplexes is often ascribed to the entrapment and degradation of siRNA payload in the endosomal compartments. A possible mechanism by which polyplexes rupture the endosomal membrane and release their nucleic acid cargo is commonly defined as the "proton sponge effect". This is an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
159
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 189 publications
(162 citation statements)
references
References 40 publications
1
159
1
1
Order By: Relevance
“…After internalization, polyplexes are known to be trafficked through the endolysosomal pathway with different possible fates, such as lysosomes, Golgi or recycled vesicles. 41,42 Lastly, we observe polyplexes mostly in the perinuclear region (t [12][13][14][15][16][17][18][19][20][21][22][23][24] ), the fate of the non-recycled polyplexes. This localization has been proposed to be the previous step to nuclear entry.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…After internalization, polyplexes are known to be trafficked through the endolysosomal pathway with different possible fates, such as lysosomes, Golgi or recycled vesicles. 41,42 Lastly, we observe polyplexes mostly in the perinuclear region (t [12][13][14][15][16][17][18][19][20][21][22][23][24] ), the fate of the non-recycled polyplexes. This localization has been proposed to be the previous step to nuclear entry.…”
Section: Resultsmentioning
confidence: 84%
“…2c). However, at later time points, we could only observe discrete pDNA not covered by the polymer (t [12][13][14][15][16][17][18][19][20][21][22][23][24] ), making it evident that the pDNA release has occurred after a few hours of internalization. Moreover, we observed a reduction in the amount of the free polymer that, as mentioned previously, enters rapidly in the cell.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Mitani et al have shown that oral administration of ESG suppresses dextran sulfate sodium‐ and 2,4,6‐trinitrobenzenesulfonic acid‐induced colitis and oxidative stress in mice, suggesting that ESG could prevent inflammatory bowel disease. Interestingly, as natural glycogen is typically only present in the cytoplasm, there is limited data on the uptake pathway of exogenous glycogen nanoparticles into cells . A recent study by Ida‐Yonemochi et al showed that uptake of ESG into MC3T3‐E1 cells was accompanied with an increase in expression of the glucose transporter 1 (GLUT‐1) protein, and when this protein was inhibited, the ESG particles mainly aggregated on the cell surface, with some particles internalized by endocytosis (Figure G–I).…”
Section: Functionalizing Glycogen Nanoparticlesmentioning
confidence: 99%
“…The structures of polysaccharides vary considerably but span from linear to highly branched polymers with molecular weights ranging from thousands to millions, composed of mono‐ or disaccharides, or short‐chain oligomers bound together by glycosidic linkages . There is a rich history of research on the use of polysaccharides in a range of therapeutic applications including: i) soft tissue engineering, where the materials can be designed to mimic the mechanical properties of the extracellular matrix in the tissue; ii) as drug, protein, or gene delivery systems, where polysaccharides have a large number of reactive groups that allow for tunable properties such as pH‐responsiveness; and iii) as nanoprobes for cellular and tissue imaging . Of the available polysaccharides, the most studied biopolymers for use as therapeutic materials are arguably derivatives or composites of cellulose, chitosan, hyaluronic acid, and/or alginate .…”
Section: Introductionmentioning
confidence: 99%